THUNDERSTORM AND RAINFALL ACTIVITY OVER KHYBER PAKHTUNKHWA (KPK), PAKISTAN - Sadiq, N. (The Nucleus, 2012)
Fifty years (1961–2010) of thunderstorm (TS) and rainfall (RF) occurrence days for 11 available meteorological observatories of Khyber Pukhtunkhwa (KPK) spread over the province were used to obtain their monthly, overall seasonal and station wise seasonal percentages from all KPK totals. The monthly study has revealed two marked peaks of TS and RF while rainfall activity in end of winter and start of premonsoon is greater than in peak monsoonal months. Overall seasonal analyses of these two parameters suggest that rainfall yield associated with post-monsoon season, TS seems to be higher than the premonsoon season. Station wise seasonal analyses of winter indicate that all stations acquire much more RF accompanied with very little TS activity. The situation is altogether different during premonsoon and monsoon while in post-monsoon, the situation is rather complex. The present study will promote various components of TS and RF activity over KPK and will help the weather forecasters, aircraft pilots, agriculturists and planners in this respect.